Social portrait of a successful Belarusian employee in the context of digitalisation of society: professional digital competencies and personal competitiveness - Deniskina, Anna I. (Journal of the Belarusian State University. Sociology, 2024)
The process of digitalisation observed in all spheres of professional activity is being investigated. A descriptive model of the evolution of key factors of employee competitiveness is presented. The formation of a new architecture of demanded professional competencies and the associated social risks are considered. The methodology of sociological research of professional digital competencies is proposed. It is noted that in the conditions of modernisation of enterprises, increasing the personal competitiveness of an employee through the development of digital skills will ensure his timely integration into the socio-economic structure of the digital labour market.